(untitled) (Comparative Professional Pedagogy, 2021)
The article is devoted to the development of primary school students’ emotional intelligence. The concept of “emotional intelligence” is quite new to pedagogical science, it was first introduced in the 1990s in the studies of American psychologists J. Mayer and P. Seloway. It was analysed that the understanding of scientists of emotional intelligence is based on the emotional component of personality and is the ability to understand own and others’ emotions, the ability to control them and interpret them correctly through non- verbal signals. It has been found that the American journalist D. Goleman’s approach to understanding emotional intelligence is based on a combination of cognitive abilities and personal characteristics of the individual. The author reveals the main results of education that need to be considered in the process of developing the content of emotional intelligence education in educational institutions, such as: awareness of their own emotions, self-control or control of their own emotions, personal motivation, empathy, management of social relations. Examples of tasks that can be used in primary school to develop students’ emotional intelligence are presented in the article. The views of foreign scientists on the development of emotional intelligence of primary school students are given. The international educational program of social and emotional learning (SEL) aimed at the implementing of emotional learning in general secondary education institutions and the results of its work are analysed. The purpose of SEL is to form five basic competencies in the field of emotional education, namely: self-awareness, self-organization, social consciousness, building relationships and making responsible decisions. Early school age is characterized by sensitivity and emotionality, which is a favourable condition for the development of emotional intelligence. It is proved that the child’s understanding of their own emotions has a positive effect on the socialization and self-realization of students, as well as on their academic success.